Impacts and synergies of weather index insurance and microcredit in rural areas: a systematic review - Yu Lu; Lu Yu; Wenjun Li; Aleksandrova, Mariya (Environmental Research Letters, 2022)
Weather constitutes a major source of risks facing households in rural areas, which are being amplified under climate change. In this context, two main rural financial services, weather index insurance and microcredit, have been increasingly adopted by farmers worldwide. However, the understanding of the socioeconomic and ecological impacts of these rural finance schemes, including potential maladaptive outcomes, remains ambiguous. We review the recent literature on weather index insurance and microcredit for farmers and find that both rural financial services have positive economic impacts, though benefits to the poorest populations remain controversial. Moreover, their impacts on the ecological systems are less studied and are found to be mainly negative. In addition, considering that both financial instruments have strengths and limitations, we argue that combination schemes (e.g. a hybrid product) may generate positive synergistic effects on building socioeconomic resilience to climate risks in agricultural regions. However, this may also add new economic risk to local financial institutions. This comprehensive review provides a reference for the potential benefits and risks of agricultural finance innovations. Further studies on the ecological impacts of rural financial services and the synergistic effects of the combination on socioeconomic and ecosystem resilience in rural contexts are needed to fill the current research gap.